Recent update of percutaneous radiologic jejunostomy - Charles Y. Kim; Ji Hoon Shin (Society of Gastrointestinal Intervention, 2021)
Although percutaneous radiologic jejunostomy has not been widely accepted as a primary insertion technique due to the technical difficulty for inexperienced operators, it may be a crucial procedure for patients with previous gastrectomy or an otherwise inaccessible stomach, particularly in patients who are not candidates for a surgical jejunostomy. Targeting the appropriate target jejunal loop and affixing the bowel with a t-fastener anchor are the most important and challenging technical steps. Technical success rate ranged from 92% to 100% based on 19 to 106 patients in several representative reports, with major complications ranging from 3.9% to 13.0%.